Implementasi Model Pembelajaran Cooperative Integrated Reading and Composition dalam Meningkatkan Kemampuan Membaca dan Menulis al Qur’an Siswa di SDN Tanah Kali Kedinding V Surabaya - Aminah, Siti (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2019)
The skill of reading and writing the Qur'an is an aspect that is very important in Islamic Religious Education (PAI) lessons. Because the Qur'an is the basis as well as the main instrument in PAI learning in schools at every level. Therefore, in improving the competence of reading and writing skills The Qur'an in students, the use of the CIRC learning model (Cooperative Integrated Reading and Composition) can be alternatives in today's teaching and learning process. The main problem In this study is an effort to improve skills reading and writing the Qur'an with the CIRC (Cooperative Integrated Reading and Composition) third grade students of SDN Tanah Kali Kedinding V Surabaya. Based on the results of the data analysis, the findings This research is that the Cooperative learning model Integrated Reading and Composition can bridge students in improving the skills of writing and reading the Qur'an. From the average results, students' ability to read and write the Qur'an There was an increase from the previous 79 to 85, from the value of Minimum Completeness Criteria (KKM) for Religious Education subjects Islam which reached 80. So that the Cooperative Integrated method Reading and Composition (CIRC) has a positive impact on combining the skills of reading and writing the Qur'an for students grade III SDN Tanah Kali Kedinding V Surabaya.